Preseismic Groundwater Ion Content Variations: Observational Data in Flowing Wells of the Kamchatka Peninsula and Conceptual Model - Galina Kopylova; Svetlana Boldina (Minerals, 2021)
Repeated manifestations of hydrogeochemical anomalies in groundwater ion content variations before local strong earthquakes were recorded in three flowing wells of the Petropavlovsk-Kamchatsky test site. A model of changes in chemical composition of groundwater is considered using observational data and modeling of two waters mixing with contrasting composition in a zone of increased permeability in aquifer. Hydrodynamic parameters of the model—relaxation time of water pressure impulses and the time of mixed water movement in aquifer and wellbore—can vary from days to hundreds of days in individual wells. These parameters determine the duration and morphological features of anomaly in mixed water from a well. Using observational data from self-flowing well M-1, an assessment was made of chemical composition and mineralization of two mixing waters and their ratio in mixed water under background conditions and during the preparation of earthquake on 2 March 1992, Mw = 6.9.